ARTIFICIAL INTELLIGENCE AND ARGUMENTATIVE MODALITIES IN TEXTS GENERATED BY CHATGPT - Oliveira Silva, Franklin; Pereira da Silva , Francisca Silveline (Revista de Letras, 2025)
This article aims to analyze the argumentation in texts prepared with the help of ChatGPT chatbot, using the notions of argumentative modalities (Amossy, 2018) and referencing (Cavalcante et al., 2022). Methodologically, the corpus collected by Silva e Silva (2024) was used in the analysis of the essays of the National High School Examination (ENEM) generated by the same chatbot. The research revealed that generative artificial intelligence can imitate the argumentative prototype expected for the textual genre of ENEM. However, the vocabulary presented is considerably less than what is expected of a candidate in this context. This study highlights the ability of ChatGPT to reproduce complex argumentative structures, but also highlights its limitations in terms of lexical richness. These results underline the importance of a robust vocabulary for academic text production and suggest that, although AI can be a useful tool, it does not replace human mastery over language.